(untitled) (Journal of Engineering, 2010)
A three-dimensional coupled finite element analysis algorithm is developed to predict the behaviour of single piles in clay. Three dimensional 20-noded brick elements are used in the analyses carried out on three documented field studies. Each node carries four degrees of freedom, three being for displacements in the three perpendicular space dimensions while the fourth is allocated for pore water pressure. The behaviour of the material of the pile is idealized through a linear elastic constitutive relationship while that for the soil by the Modified Cam-Clay model both extended to cover three-dimensional characteristics. The load-displacement results from the developed algorithm on the three selected problems from literature show a very good agreement with the observations. Moreover, the build-up of pore fluid pressures and their dissipations were found to be consistent with field measurements also.